Exploring the problems and needs of repeaters in learning ESL writing: a case stduy - Kassim, Rosnani; Md. Zamin, Ainul Azmin; Kamaruddin, Mohd Fauzi (Science and Engineering Research Support Society, 2019)
The purpose of this research was to find out the problems faced by repeaters in learning writing in English in a pre-sessional course at an international university. The case study involved two students who had repeated the same writing course in three consecutive semesters. The research had two main objectives. One was to explore the challenges the repeaters faced in learning second language writing and the other was to elicit their needs with regard to learningthat particular skill. The main data collection method was face-to-face semi-structured interviews. With regard to the difficulties that the repeaters facedin learning ESL writing, they highlighted low motivation and their inability to identify their ownweaknesses in writing as their main challenges. They also pointed that these problems were further aggravated by lack of support from their teachers. In terms of their needs, the repeaters cited that they would want individual help and support from their writing teachers so that they could learn and perform better. IT can be concluded that the roles played by teachers are vital in enhancing the quality of the repeaters’ learning process and experience.